Rapid Determination of SARS-CoV-2 antibodies using a bedside, point-of-Care, serological test. Issue 1 (1st January 2020) - Dortet, Laurent; Emeraud, Cecile; Vauloup-Fellous, Christelle; Khecharem, Mouna; Ronat, Jean-Baptiste; Fortineau, Nicolas; Roque-Afonso, Anne-Marie; Naas, Thierry
ABSTRACT: Background : Several serological tests for SARS-CoV-2 have been developed or use, but most have only been validated on few samples, and none provide medical practitioners with an easy-to-use, self-contained, bedside test with high accuracy. Material and methods : Two-hundred fifty-six sera from 101 patients hospitalized with SARS-CoV-2 infection (positive RT–PCR) and 50 control sera were tested for IgM/IgG using the NG-Test IgM-IgG COVID all-in-one assay. The seroconversion dynamic was assessed by symptom onset and day of RT–PCR diagnosis. Results: Among the SARS-CoV-2 infected patients, positive IgG and/or IgM result was observed for 67.3% of patients (68/101), including 17 (16.8%) already positive at the day of RT–PCR, and 51 (50.5%) with observable seroconversion, and 32.7% (33/101) remained negative as subsequent sampling was not possible (patient discharge or death). The sensitivity increased with the delay between onset of symptoms and sampling, going from 29.1%, 78.2% and 86.5% for the time periods of 0-9-, 10-14- and >14-days after the onset of symptoms, respectively. Cumulative sensitivity, specificity, Positive Predictive Value and Negative Predictive Value were 97.0%, 100%, 100% and 96.2%, respectively 15-days after the onset of symptoms. No difference in seroconversion delay was observed regardless of whether patients received ventilation. Conclusions: The NG-test is a bedside serological assay that could serve as a complementary source of diagnostic information to RT–PCR and chest imaging. It may also be useful to monitor immunological status of medical and non-medical workers during the ongoing pandemic, and the general population after social distancing measures have eased.